The burden of incontinence in a real-world data environment: insights from a digital patient companion - Au, Alexandra von; Wallwiener, Stephanie; Matthies, Lina; Friedrich, Benjamin; Keim, Sabine; Wallwiener, Markus; Reisenauer, Christl; Brugger, Sarah (International urogynecology journal, 2022)
Introduction and hypothesis Urinary incontinence (UI) has a potentially devastating effect on women’s quality of life (QoL). Conservative treatment by means of pelvic floor muscle training is the first-choice treatment modality. Nowadays, this can be supported by digital apps like pelvina©—a digital health companion pelvic floor course. - Methods Using pelvina©, UI symptoms and QoL are regularly examined through the questionnaires QUID and SF-6D. Subsequently, we analyzed the incidence and degree of UI and its impact on QoL in 293 users in a real-world environment. - Results The 293 patients included in this study had a median age of 36 years and a median of two children. Patients were slightly to moderately affected by UI with a QUID of 6 (2-11, maximum 24). Age and number of children were independently associated with the incidence of UI with an adjusted odds ratio (aOR) of 1.06 (95% CI 1.01-1.12) and aOR of 1.86 (95% CI 1.12-3.08). The severity of UI strongly correlated with impairment of QoL (ρ = 0.866, P < 0.001). - Conclusions The use of real-world data generated by digital health solutions offers the opportunity to gain insight into the reality of patients’ lives. In this article, we corroborate the known associations between number of children and UI as well as the great influence UI has on QoL. This study shows that, in the future, the use of digital apps can make an important contribution to scientific data acquisition and, for example, therapy monitoring.